Contribution of Academic Self Concept and Locus of Control to The Learning Habits - Afni Rizkah Pulungan; Marjohan Marjohan (Universitas Negeri Padang, 2020)
This research was motivated by the low learning habits of students in school. The concept of academic self and locus of control are factors that are thought to influence learning habits. This study aims to illustrate the contribution of academic self-concept and locus of control to the learning habits of students in school. This research uses descriptive quantitative methods. Samples in this study 162 students selected using proportional random sampling techniques The instruments used in this study were likert scales on variables of academic self-concept and learning habits, on locus of control variables using internal-external inventory Rotters locus of control (I-E) scales. The findings of this study show that: (1) the average academic self-concept is in a moderate category, (2) locus of control is also in the high category, (3) learners' learning habits are categorized well, (4) academic self-concept contributes to learning habits by 36.3%, (5) Locus of control contributes to learning habits by 10.6%, and (6) academic self-concept and locus of control together contribute 36.4% to learners' learning habits. The study findings show that: (1) on average, academic self-concept is in the high category, (2) locus of control in the internal category, (3) learners' learning habits in the good category, (4) academic self-concept contributes to learning habits, (5) locus of control does not contribute to learning habits, and (6) academic self-concept contributes to learners' learning habits, and internal locus of control does not contribute to learning habits because it already leads to locus of external control. The implications of the research results can be used as an analysis of the needs in guidance and counseling services at SMA Negeri 13 Padang.